Addressing Global Inequality through Modern Macroeconomic Approaches - Paulina; Adiawaty, Susi (Moneta : Journal of Economics and Finance, 2024)
This narrative review examines the theoretical and empirical developments in macroeconomic thought, focusing on the limitations of conventional models and the emergence of more inclusive and adaptive approaches. The study aims to explore how contemporary macroeconomic theory can better address global inequality, economic volatility, and institutional transformation. Using a structured literature search across Scopus, Google Scholar, and PubMed, the review employed specific keywords such as "macroeconomic theory," "Keynesianism," "policy implications," and "regulatory economics." Inclusion criteria prioritized peer-reviewed articles published within the last 15 years, focusing on diverse macroeconomic schools of thought and their real-world applications. Findings reveal the sustained relevance of Keynesian models, especially during economic crises such as the COVID-19 pandemic, where fiscal interventions played a pivotal role. Criticism of Dynamic Stochastic General Equilibrium (DSGE) models is validated by their inability to reflect social complexities and economic uncertainties. In contrast, agent-based modeling (ABM) offers a more nuanced understanding of economic dynamics. Furthermore, the role of institutional reform in shaping inclusive and sustainable macroeconomic policies is emphasized, particularly in the context of developing countries. The integration of economic, ecological, and ethical dimensions in the "beyond-GDP" framework signals a shift toward a more holistic economic paradigm. These insights underscore the need for continued innovation in macroeconomic modeling and policy design. By adopting interdisciplinary and context-sensitive approaches, policymakers and researchers can better address the structural and systemic challenges of the 21st century.